Dampak Implementasi Model Collaborative Problem Solving pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Abiyyu Arkan Muhammad; Irma Husnaini (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
The purpose of this research is to know the impact of implementing a collaborative problem-solving model on learning outcomes of the basics of electrical engineering of students in class X at SMK Dhuafa Padang. This research uses a quantitative approach in the form of a pre-experimental design with a one-group pretest-posttest design. The subjects in this research were 15 students of X grade TITL at SMK Dhuafa Padang. The instrument used in this research is multiple choice test questions, which are prepared based on the material and learning objectives to be achieved according to the curriculum. In this research instrument testing was carried out to determine the validity, reliability, level of difficulty of the questions, and the differentiating of the questions. The data analysis technique used is Classical Completeness of Student Learning Outcomes and Effect Size analysis. Based on the results of research and discussions that have been carried out, the average value of student learning outcomes taken from the post-test assessment has increased. The effect size was in a large category, so it can be said that the collaborative problem-solving model has a big impact on learning outcomes. However, for Classical Completeness of Student Learning Outcomes does not reach the minimum percentage. Other impacts received by students after implementing the treatment are that students are more active in discussing with their friends so that learning is more easily productive, helps build thinking skills, can implement problem-solving, build a positive atmosphere, and encourage or motivate other students